Analysis of Hapanasan Water Tourism Management Strategies Facing the Post-COVID-19 Pandemic Period Rambah Tengah Hulu Village, Riau Province - Marini Yunita; Himawan Brahmantyo; Sri Mariati (Edumaspul: Jurnal Pendidikan, 2023)
The Covid-19 pandemic has had a negative impact on various tourism sectors. In the implementation of tourism destination management by Rokan Hulu Regency, strategic steps such as improving facilities, building new facilities for the convenience of tourists, supervision for compliance with health standards to reduce the spread of Covid-19, are less carried out by the management. This study aims to analyze how the management of water Hapanasan tourism destinations faces the conditions of the Covid-19 pandemic, to identify and analyze the current management of water Hapanasan, and to find out the strategy of sustainable management of water Hapanasan tourism destinations. Population is the entire hot water tourism object Rambah Tengah Hulu Village, Riau Province The sample used in this study is purposive sampling. To achieve this goal, the author uses descriptive qualitative methods, with observation, in-depth interviews with key persons, and literacy as data collection methods. The results of this study show that the management carried out did not run smoothly so that many facilities were abandoned during the pandemic, but when it was loose, managers began to repair damaged facilities and return to maintain them, and there was no sustainable management strategy after the Covid-19 pandemic. The results of this study will have implications for improving the quality of tourism infrastructure, management strategies that can be done in tourist destinations, managing human resource capabilities. All of that can make water Hapanasan a sustainable tourism destination.